Modernization of Administration of Parking Tax Collection with Tapping Box as A Supervision and Compliance Function of Regional Taxpayers in Bekasi City - Mainita Hidayati; Wuwuh Andayani; Ratih Kumala; Agus Subagiyo; Pebriana Arimbhi (Yayasan Ilomata, 2021)
Tax modernization seems to be very necessary in the current digital era. This considers that taxes are one of the largest sources of tax revenue, both in the central and regional regions. This study focused on the scope of the Regions, one of the sources of Regional Tax is parking tax. The phenomenon that occurred in this study was the low acceptance of Parking Tax on Regional Taxes. In order to increase regional income and prevent any leakage of funds, the Bekasi City Regional Revenue Agency has installed a data management application in several places of business, namely Tapping Box. Tapping Box is a machine or transaction recording device that can record all transaction data that occurs and sends it to the Bekasi City Regional Revenue Agency server through the Global System for Mobile network (GSM). The purpose of installing the Tapping Box is as a means of monitoring and testing taxpayer compliance that displays the financial reports of transaction in a transparent and accountable way. This study used a descriptive type of research with a qualitative approach. Also, the data was analyzed by using qualitative method. The results of this study indicated that parking tax supervision has not gone well because there were still some taxpayers who have not installed the Tapping Box. The result of this Tapping Box installation is that the realization of parking tax receipts has not reached the set target, but the parking tax revenues have increased comparing to those in the previous year. Moreover, if the installation of the Tapping Box is evenly distributed, the parking tax revenue will be maximized.